New clinical and organizational approaches to preventing cardiovascular diseases in the primary health care system - S A Boĭtsov; A M Kalinina; P V Ipatov (Терапевтический архив, 2013)
The paper deals with the justification and description of clinical and organizational approaches to preventing cardiovascular diseases (CVD) in the primary health care system (PHCS) under the present conditions of health care modernization in Russia. It formulates the basic directions of systematic measures in integration strategies for the prevention of noncommunicable diseases (mainly CVD) at a federal level, in which practical measures are presented to improve a system for the early detection of high-risk individuals and to carry out measures for risk factor correction in PHCS, i.e. to implement high-risk strategies, including clinical and organizational approaches to reconstituting the medical prevention infrastructure in PHCS. This is favored by the new normative documents adopted by the Ministry of Health of Russia on the follow-up and prophylactic medical examinations of the adult population. The paper substantiates the objective need for such examinations and characterizes the main clinical and organizational approaches promoted in medical examinations, which is aimed at introducing the current science-based and economically expedient methods in the real practice of PHCS for the early identifications of atherosclerosis-induced major CVDs and, what is particularly important, a risk for their development. Prophylactic counseling as a compulsory component is first being introduced in medical examination procedures. The key clinical and organizational principle of effective CVD prevention in public health is the implementation of the relationship and continuity of preventive measures, which becomes realistic with the adoption of new regulations of clinical examinations, prophylactic medical examinations, and follow-ups. The improvement of CVD prevention is associated not only with the introduction of organizational innovation changes, but also with the need to create a prevention ideology in physicians at all levels. It is emphasized that a comprehensive approach and all integrated CVD prevention strategies both at the population level and in the PHCS facilities are the most efficient and cost-effective procedure to reduce premature deaths from CVD in the population and to improve the demographic situation in our country.